Drivers of Indonesia's Foreign Exchange Reserves and Their Linkage to USD Liquidity: Evidence From A Macro-Financial Ols Model - L M Agung B Banyu Garmada; Jagat Prirayani (Green Publisher Indonesia, 2026)
Indonesia's foreign exchange reserves are an important shield to maintain currency stability and protect the country's financial system. In recent years, changes in global interest rates, commodity prices, capital movements, and local financial conditions have made it difficult to manage these reserves. These changes create important questions for policymakers about which macro-financial factors have the strongest impact on Indonesia's foreign exchange reserves and how they relate to the USD's liquidity in the domestic interbank market. This study was conducted on the assumption that foreign exchange reserves and interbank USD liquidity respond simultaneously to domestic financial conditions and global financial macro turmoil. Based on the international financial literature, this study develops the proposition that domestic market yields, global dollar strength, financial stress indicators, commodity cycles, and external sector performance together determine the monthly dynamics of Indonesia's foreign exchange reserves and USD liquidity. The analysis applied multivariate Ordinary Least Squares to monthly macrofinancial data from 2010 to 2024, preceded by stationarity testing, multicollinearity diagnostics, and residual evaluation. The results show that Indonesia's foreign exchange reserves are heavily influenced by long-term domestic yields, global USD indices, interbank liquidity conditions, export performance, US inflation, and global dollar funding stress. Interbank USD liquidity is attributed to trade balances, domestic and global yields, consumer confidence, retail activity, MSCI equity performance, global commodity cycles, and United States corporate credit conditions. This research provides a data-driven starting point that can support the development of more responsive policy instruments to protect Indonesia's external stability.